The Relationship Between Protein Intake And Blood Hemoglobin Levels In Adolescent Girls In Jatirogo Sub-District - Ni'ma, Nada Rizqina; Fauziah, Lilia Faridatul (Universitas Negeri Medan, 2024)
Hemoglobin levels in the body should be at a normal value. If hemoglobin levels decrease, anemia will result. One of the factors that encourage nutritional anemia in adolescents is chronic infectious diseases, menstruation, sudden bleeding such as accidents and the amount of food or poor absorption of iron, vitamin B12, vitamin B6, vitamin C and copper. This study aims to determine the relationship between protein intake and blood hemoglobin levels in adolescent girls in Jatirogo District. Analytic research method with cross sectional approach. The population of this study amounted to 763 respondents with a sample of 263 adolescents, determined by cluster random sampling tectics. Independent variable of protein intake and dependent variable of hemoglobin level. The research analysis used Spearmans correlation statistical test. The results showed that most of the protein intake included a severe deficit. The results of the statistical test of protein intake p-value = 0.023 <0.05 indicate that there is a significant relationship between protein intake and hemoglobin levels in the blood. From the description above, it can be concluded that the lower the protein intake, the lower the hemoglobin level. In addition, the longer the period with a long time, the lower the hemoglobin level in adolescent girls in Jatirogo District.